Structural evaluation for the historic Palace of King Ghazi and mechanism of its rehabilitation. (December 2020) - Al-Sibahy, Adnan; Edwards, Rodger
Abstract: This paper presents a methodology of structural evaluation for the ancient palace of King Ghazi throughout site inspection, field and laboratory measurements using both non and semi-destructive tests followed by structural analysis. A suitable repair technique is then suggested. The site investigation was planned to identify the construction method for the structural elements of the palace, the critical failure zones and the locations of cracks. On the other hand, the experimental programme focused on measuring the compressive strength of both walls and columns based upon the rebound hammer and ultrasonic pulse velocity tests. The test results were validated against the calculated compressive strength resulting from testing of brick units and gypsum mortar taken form the same site. A comparison was also made with the relevant codes of practice. The site inspection showed that the major parameters governing distress of the palace were the absorption of the moisture, changes of the atmospheric conditions and vehicle or man hand accidents. A unique composition was adopted in construction of the roof which includes layer of jack-arching combined with a steel plate-wooden frame. The width of the walls was sufficient to reduce the imposed stresses on the soil where 0.5 m was used in the main part of the palace. The experimental results showed that both rebound hammer and ultrasonic pulse velocity tests can give approximately similar compressive strength values for the walls and columns. Minimal variations were noted in the measured strength along the tested walls and columns and the average compressive values reached 6.02 MPa and 4.3 MPa, respectively. The calculated values of compressive strength form the wall components (brick units and gypsum mortar) revealed close agreement with those measured using nondestructive tests for the whole walls. No influential defects were noted throughout the structural analysis and the palace seem to be in a stabile manner. A suitable rehabilitation technique was suggested based upon the outputs of the structural analysis and experimental measurements.